MicroRNA-22 Controls Aberrant Neurogenesis and Changes in Neuronal Morphology After Status Epilepticus - Beamer, Edward H.; Jurado-Arjona, Jeronimo; Jimenez-Mateos, Eva M.; Morgan, James; Reschke, Cristina R.; Kenny, Aidan; de Leo, Gioacchino; Olivos-Oré, Luis A.; Arribas-Blázquez, Marina; Madden, Stephen F.; Merchán-Rubira, Jesús; Delanty, Norman; et al. (Frontiers in Molecular Neuroscience, 2018)
Prolonged seizures (status epilepticus) may drive hippocampal dysfunction and epileptogenesis, at least partly, through an elevation in neurogenesis, dysregulation of migration and aberrant dendritic arborization of newly-formed neurons. MicroRNA-22 was recently found to protect against the development of epileptic foci, but the mechanisms remain incompletely understood. Here, we investigated the contribution of microRNA-22 to status epilepticus-induced aberrant adult neurogenesis. Status epilepticus was induced by intraamygdala microinjection of kainic acid to model unilateral hippocampal neuropathology in mice. MicroRNA-22 expression was suppressed using specific oligonucleotide inhibitors (antagomir-22) and newly-formed neurons were visualized using the thymidine analogue iodo-deoxyuridine (IdU) and a GFP-expressing retrovirus to visualise the dendritic tree and synaptic spines. Using this approach, we quantified differences in the rate of neurogenesis and migration, the structure of the apical dendritic tree and density and morphology of dendritic spines in newly-formed neurons. Status epilepticus resulted in an increased rate of hippocampal neurogenesis, including within the undamaged contralateral dentate gyrus. Newly-formed neurons underwent aberrant migration, both within the granule cell layer and into ectopic sites. Inhibition of microRNA-22 exacerbated these changes. The dendritic diameter and the density and average volume of dendritic spines were unaffected by status epilepticus, but these parameters were all elevated in mice in which microRNA-22 was suppressed. MicroRNA-22 inhibition also reduced the length and complexity of the dendritic tree, independently of status epilepticus. These data indicate that microRNA-22 is an important regulator of morphogenesis of newly-formed neurons in adults and plays a role in supressing aberrant neurogenesis associated with status epilepticus.